Comer e sobreviver: a comida como cenário de refugiados sírios em São Paulo - Marchini, Lize Navarro (2022)
The research observes two forced displacement experiences of Syrian refugees in the city of São Paulo, whose main source of income is the sale of typical food from their place of origin. The commercialization of food by the research interlocutors takes place through orders, mobilizing networks of indications, participation in fairs of nations and cultures of different institutions and through direct sales within the establishment of one of the families. Using the ethnographic observation of routines related to food and its commercialization, it is possible to notice variations in the spaces and discourses mobilized about the history of displacement itself and what is considered a typical element of a place. The nuances about the experience indicate important paths for anthropological investigation, and the questions raised here do not exhaust the possibilities for reflection on the connection between the themes from the perspective of exoticization.